2016
DOI: 10.1098/rsbl.2016.0368
|View full text |Cite
|
Sign up to set email alerts
|

Climate change is projected to outpace rates of niche change in grasses

Abstract: Climate change may soon threaten much of global biodiversity, especially if species cannot adapt to changing climatic conditions quickly enough. A critical question is how quickly climatic niches change, and if this speed is sufficient to prevent extinction as climates warm. Here, we address this question in the grass family (Poaceae). Grasses are fundamental to one of Earth's most widespread biomes (grasslands), and provide roughly half of all calories consumed by humans (including wheat, rice, corn and sorgh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 21 publications
2
23
0
Order By: Relevance
“…Nevertheless, important questions remain unanswered. First, do these results apply to other organisms besides vertebrates, such as arthropods (which include most described species) and plants (on which most species depend, including humans; for some plant results see [24])? Second, do they apply to shorter time scales?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, important questions remain unanswered. First, do these results apply to other organisms besides vertebrates, such as arthropods (which include most described species) and plants (on which most species depend, including humans; for some plant results see [24])? Second, do they apply to shorter time scales?…”
Section: Introductionmentioning
confidence: 99%
“…One approach for estimating past rates of change in climatic niches is to compare niches among closely related species using time-calibrated phylogenies [23,24]. For example, Quintero & Wiens [23] analysed rates of change among 540 terrestrial vertebrate species, using climatic data from their current geographic ranges.…”
Section: Introductionmentioning
confidence: 99%
“…7 This is concerning because grassland is one of the most widespread biomes in the world, supporting many endemic species. 8 Specifically, calcareous grasslands are among the most diverse and threatened plant communities in Europe, 9,10 containing between 20 and 50 different vascular plants per square metre, many of them rare or threatened. 9 Therefore, calcareous grassland is an ecosystem of high conservation value 10,11 and high aesthetic appeal.…”
Section: Introductionmentioning
confidence: 99%
“…Before the selection of a few species that led to complete domestication, experimentation with multiple grass species occurred in multiple places across the Fertile Crescent region for centuries [24]. Even then, at the end of the day, looking for new grasses with the potential to replace the staple grains of the past 20,000 plus years may be an exercise in futility (or another wicked problem), if the survival of all Poaceae in these times of climate change is threatened [20].…”
Section: Human Adaptation and Resilience To Changing Climatementioning
confidence: 99%
“…In forecasting shifting climate scenarios to 2070, it was found that Poaceae as a family is unlikely to adapt through climate niche change and migration to more amenable habitat [20]. This is particularly troublesome given that maize, rice and wheat are not only the major plants cropped globally, they currently account for 89% of all cereal production, and supplied 42% of all the calories consumed by humans in 2009 [21].…”
Section: Human Adaptation and Resilience To Changing Climatementioning
confidence: 99%